2008
DOI: 10.1093/gerona/63.12.1299
|View full text |Cite
|
Sign up to set email alerts
|

Diminished Acute Phase Response and Increased Hepatic Inflammation of Aged Rats in Response to Intraperitoneal Injection of Lipopolysaccharide

Abstract: Aging is associated with a deterioration of the acute phase response to inflammatory challenges. However, the nature of these defects remains poorly defined. We analyzed the hepatic inflammatory response after intraperitoneal administration of lipopolysaccharide (LPS) given to Fisher 344 rats aged 6, 15, and 22-23 months. Induction of the acute phase proteins (APPs), haptoglobin, alpha-1-acid glycoprotein, and T-kininogen was reduced and/or retarded with aging. Initial induction of interleukin-6 in aged rats w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 62 publications
(41 reference statements)
0
9
0
Order By: Relevance
“…The incidence of chronic inflammatory diseases appears to increase during the aging process . Mice also show a propensity for age‐related periodontal disease, which correlates with increased production of interleukin‐17 and elevated numbers of periodontal neutrophils .…”
Section: Interleukin‐17 and Inflammatory Bone Lossmentioning
confidence: 99%
“…The incidence of chronic inflammatory diseases appears to increase during the aging process . Mice also show a propensity for age‐related periodontal disease, which correlates with increased production of interleukin‐17 and elevated numbers of periodontal neutrophils .…”
Section: Interleukin‐17 and Inflammatory Bone Lossmentioning
confidence: 99%
“…Both the mitochondrion and NADPH oxidase isoforms are potential sources of ageing‐related excessive ROS production [16,17]. The reduction or abrogation of age‐associated pathologies via anti‐oxidant supplementation [18] or by overexpression of cellular anti‐oxidant defence enzymes in mitochondria [19,20] supports this concept, although this wisdom has been challenged recently in mice [4]; the overexpression of major anti‐oxidant enzymes was shown to be insufficient to extend their lifespan. A number of species‐specific differences in the innate immunity and macrophage biology have been documented that are relevant to ageing and warrant caution in the extrapolation of observations between species (reviewed previously [21,22]).…”
Section: Free Radicals and Ageingmentioning
confidence: 99%
“…Similarly, a poor acute phase protein response has been described in ageing mice in response to inflammatory challenge and is associated with significant tissue damage [4,5]. Paradoxically, circulating levels of the inflammatory cytokines, particularly of the acute phase protein inducer interleukin (IL)‐6, are enhanced, although it is unclear whether downstream signalling following ligand–receptor interaction maintains its efficiency with ageing [4,5]. Cross‐talk exists between the innate immune system and the acquired immune system through shared receptors; Toll‐like receptor (TLR)‐mediated priming of T cell and B cell responses enhances development [6–8] of the acquired immune response, therefore age‐related dysfunction of TLR function could potentially impact upon the effectiveness of both the innate and acquired immune systems.…”
Section: Introductionmentioning
confidence: 99%
“…In a previous report, preliminary evidence suggested that the degree of reduction in plasma T-kininogen levels was directly related to the severity of impaired liver function [81]. Recent results showed that aged rats present reduced expression of T-kininogen and HP and increased hepatic injury in response to an inflammatory insult [82]. Therefore, the upregulation of HP and T-kininogen following training exercise observed in this study might be the consequence of decreased levels of markers of inflammation and oxidative stress (Figure 2) in the livers of aged rats.…”
Section: Discussionmentioning
confidence: 99%